"Cheap Energy" in Raj Patel and Jason W Moore's A History of the World in Seven Cheap Things. Issue 2 (August 2019) - Anders, Benjamin
This debates essay offers a summary and critique of the chapter "Cheap Energy" in A History of the World in Seven Cheap Things by Jason W Moore and Raj Patel. In the text of my comment, I suggest that this work—while intellectually generative—pays insufficient attention to broader analytical and theoretical debates within Global Political Economy and the study of science and technology that its analysis addresses. Additionally, the authors do not address the failure of the only major attempt to jettison the price mechanism as a system for allocating resources under conditions of industrialization—the Marxist-Leninist command economies—to generate anything approaching a sustainable society.